Strategi Kebijakan Quick Wins Berbasis Penta Helix Dalam Pemberdayaan Usaha Mikro Kecil dan Menengah di Kabupaten Majene - Hendrawan, Hendrawan; Ramadhan Antuli, Rezky; Rahmatullah, Rahmatullah; Syihabuddin Taufiq, Muhammad (Jurnal Ilmiah Administrasi Publik, 2026)
This study aims to design a quick wins policy framework based on the pentahelix model for empowering MSMEs in Majene Regency. The research employs a qualitative method with an exploratory case study design. Data collection techniques include in-depth interviews, field observations, and focus group discussions (FGDs). Data analysis is conducted using thematic analysis, content analysis, and contextual description. The selection of this method is based on the need to explore complex social phenomena. The development of MSMEs in Majene Regency requires policies capable of synergizing the roles of government, academia, business actors, the private sector/NGOs, and the media in an integrated manner. The first step to be taken is the establishment of an MSME Collaboration Forum. This policy must also be supported by integrated MSME mapping and database systems. In addition, a collaborative incentive and funding scheme, such as a matching fund, should be implemented for programs involving more than two elements of the pentahelix. Corporate CSR funds can also be directed to support MSMEs based on local potential.